2004
DOI: 10.2166/wst.2004.0390
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal in a fluidized bed bioreactor by using mixed culture under oxygen-limited conditions

Abstract: Nitrogen removal involving nitrification and denitrification was investigated in a fluidized bed bioreactor by using mixed culture sludge under oxygen-limited conditions. Methane was used as a sole carbon source for denitrification. In this study, optimal nitrification and denitrification rates were examined by varying methane and oxygen gas dissolution flow rates, 90 ml/min, 400 ml/min and 650 ml/min, in each. Simultaneously nitrification and denitrification was achieved. The total nitrogen removal rate was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The apparent specific denitrification rates observed during the continuous operation of the system were around 20 mgN g −1 MLVSS d −1 . These values were of the same order of magnitude as those reported for methane oxidation coupled to denitrification using either the aerobic pathway (15 and 90 mgN g −1 MLVSS d −1 ) or the anaerobic pathway (5 and 28 mgN g −1 MLVSS d −1 ) found by Hu et al using an enriched sludge with denitrifying methanotrophic bacteria.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The apparent specific denitrification rates observed during the continuous operation of the system were around 20 mgN g −1 MLVSS d −1 . These values were of the same order of magnitude as those reported for methane oxidation coupled to denitrification using either the aerobic pathway (15 and 90 mgN g −1 MLVSS d −1 ) or the anaerobic pathway (5 and 28 mgN g −1 MLVSS d −1 ) found by Hu et al using an enriched sludge with denitrifying methanotrophic bacteria.…”
Section: Resultssupporting
confidence: 84%
“…Denitrification coupled to methane oxidation is characterized by its low specific denitrification activity. Different authors that have used batch assays in which the aerobic pathway was promoted observed activities between 15 and 90 mgN g −1 MLVSS d −1 at temperatures of approximately 20-25 ∘ C. 15,16 For enriched NC10 sludge at 30 ∘ C, Hu et al 21 observed activities of between 8 and 17 mgN g −1 MLVSS d −1 . These values were much lower than the activity of 250 mgN g −1 MLVSS d −1 that results from the denitrification of readily biodegradable organic matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ba9 had a nitrate concentration of 0.23 ± 0.01 mg-N/L (Figure8e-f). The result of nitrogen removal can prove that B. oceanisediminis Ba9, a member of the heterotrophic nitrifying bacteria group, had a higher ammonium removal efficiency at high ammonium levels than autotrophic nitrifying bacteria[45]. The mix of two strains, B. cereus PK5 and B. subtilis PK8, had ammonium removal efficiency at 72.0% (initial 50.0 ± 1.5 mg-N/L)[46].…”
mentioning
confidence: 95%
“…They also demonstrated the feasibility of using natural zeolite as microorganism support in anaerobic fluidized bed reactor (AFBR). Khin et al (2004) tested FBR with soil as a carrier media for elimination of nitrogen by simultaneous nitrification and gentrification; 95% removal of NH 4 + -N was achieved at a hydraulic retention time (HRT) of 20 hours (Khin and Annachhatre, 2004). Aslan and Dahabb (2008) successfully operated fluidized-bed biofilm nitritation and denitritation reactors (FBBNR and FBBDR) to eliminate high concentrations of nitrogen under low dissolved oxygen.…”
Section: Introductionmentioning
confidence: 99%